(v-4nt)(v+nt)=0

Simple and best practice solution for (v-4nt)(v+nt)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (v-4nt)(v+nt)=0 equation:


Simplifying
(v + -4nt)(v + nt) = 0

Reorder the terms:
(-4nt + v)(v + nt) = 0

Reorder the terms:
(-4nt + v)(nt + v) = 0

Multiply (-4nt + v) * (nt + v)
(-4nt * (nt + v) + v(nt + v)) = 0
((nt * -4nt + v * -4nt) + v(nt + v)) = 0

Reorder the terms:
((-4ntv + -4n2t2) + v(nt + v)) = 0
((-4ntv + -4n2t2) + v(nt + v)) = 0
(-4ntv + -4n2t2 + (nt * v + v * v)) = 0
(-4ntv + -4n2t2 + (ntv + v2)) = 0

Reorder the terms:
(-4ntv + ntv + -4n2t2 + v2) = 0

Combine like terms: -4ntv + ntv = -3ntv
(-3ntv + -4n2t2 + v2) = 0

Solving
-3ntv + -4n2t2 + v2 = 0

Solving for variable 'n'.

Factor a trinomial.
(-1nt + -1v)(4nt + -1v) = 0

Subproblem 1

Set the factor '(-1nt + -1v)' equal to zero and attempt to solve: Simplifying -1nt + -1v = 0 Solving -1nt + -1v = 0 Move all terms containing n to the left, all other terms to the right. Add 'v' to each side of the equation. -1nt + -1v + v = 0 + v Combine like terms: -1v + v = 0 -1nt + 0 = 0 + v -1nt = 0 + v Remove the zero: -1nt = v Divide each side by '-1t'. n = -1t-1v Simplifying n = -1t-1v

Subproblem 2

Set the factor '(4nt + -1v)' equal to zero and attempt to solve: Simplifying 4nt + -1v = 0 Solving 4nt + -1v = 0 Move all terms containing n to the left, all other terms to the right. Add 'v' to each side of the equation. 4nt + -1v + v = 0 + v Combine like terms: -1v + v = 0 4nt + 0 = 0 + v 4nt = 0 + v Remove the zero: 4nt = v Divide each side by '4t'. n = 0.25t-1v Simplifying n = 0.25t-1v

Solution

n = {-1t-1v, 0.25t-1v}

See similar equations:

| 2x+6=1+3x | | 2x=2+44 | | -8=-3+v | | 8x^2-28x+19=0 | | 8x(2x+9)=10 | | 4(3a-4)=2(6a-9)+2 | | .5m^2+2m+8=5 | | 9y=-10 | | 9.99=0.25+113.74 | | h(t)=-16(t-6)(t+4) | | (-4+3)x=-2 | | (2x+2va)(x+3va)=0 | | 64X+80= | | 2y=1.4 | | -75x-5=2 | | Y=12-(3x+9) | | 3r+-7=5 | | 2l=40+16 | | 8+12=15 | | 2l+8=40 | | 4x+157=243 | | -3y+15=-42 | | 9x^2+18x+81=0 | | 2x^2-609=0 | | 8m-8=-8-4m-m | | (5x+2)+(10x-3)+(8x-19)+(13x-31)+(7x-11)=540 | | 40-2l=8 | | -4(-4)-16=x | | -.17x+0.2(x-2)=-0.27(1-x) | | 2x+-3(x+-1)=8 | | Y=10-1 | | 2n+1=-7+4n |

Equations solver categories